2006
DOI: 10.1071/ea05154
|View full text |Cite
|
Sign up to set email alerts
|

Residual values of soil-applied zinc fertiliser for early vegetative growth of six crop species

Abstract: Zinc (Zn) oxide is the most widely used fertiliser for the predominantly acidic to neutral soils of south-western Australia. For these soils, the residual value of Zn oxide has been determined for wheat and lupin, but not for barley, oats, canola and triticale, which are also grown in the region. Just after termination of a long-term (17 year) field experiment that measured the residual value of Zn oxide for wheat, soil samples were collected from selected plots to use in 2 glasshouse experiments. The field ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Nevertheless, Zn fertilizers do not need to be applied every year after the initial application since soilapplied fertilizers have great residual values. For example, Brennan and Bolland (2006) showed that the residual values of ZnO in a Fluventic Xerochrept could last for 10 to >17 years, depending on crop species.…”
Section: Effectiveness Of Various Methods Of Fertilizationmentioning
confidence: 98%
“…Nevertheless, Zn fertilizers do not need to be applied every year after the initial application since soilapplied fertilizers have great residual values. For example, Brennan and Bolland (2006) showed that the residual values of ZnO in a Fluventic Xerochrept could last for 10 to >17 years, depending on crop species.…”
Section: Effectiveness Of Various Methods Of Fertilizationmentioning
confidence: 98%
“…While several studies have been conducted regarding the residual effects of supplying soil-applied inorganic Zn sources to various crops (Boawn, 1974;Singh and Abrol, 1985;Brennan, 2001;Ma and Uren, 2006;Shawer et al, 2007;Alloway, 2008), only limited data are available about the residual effect of chelated fertilizers (Alvarez et al, 2009). Brennan and Bolland (2006) suggest that the residual effect of Zn in soil varied with different crop species. Flax (Linum usitatisimum L.) is a crop that is very susceptible to Zn deficiency and exhibits a notable response to the addition of Zn (Franzen, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…These reactions continue over time, reducing the long-term effectiveness of added Zn for plant production (Brennan, 1990). According to Brennan and Bolland (2006), the residual effect of Zn fertilizer applied to soil is a result of the desorption of Zn sorbed by soil constituents, the mineralization of Zn from soil organic matter, the removal of Zn from soil in agricultural produce, and/or the leaching of Zn from soil. Several environmental parameters can simultaneously influence the residual effect of Zn fertilizers: temperature, repeated drying and rewetting, soil moisture content, pH, and total metal concentration (Lock and Janssen, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The residual value of Zn fertilizer applied to soil depends on (i) removal of Zn from soil in produce (hay, grain, milk, meat, wool) (Brennan and Bolland, 2006); (ii) the continuing reactions of the applied Zn with soil constituents (Brennan, 1990;Brennan and Gartrell, 1990;Barrow, 1993); and (iii) the ability of different crop species to access Zn from soil (Graham and Rengel, 1993;Bolland, 2002, 2006). A previous field study on a sandy soil in the high rainfall (1000 mm annual average) area of the region showed that leaching losses of Zn were negligible (Brennan and McGrath, 1988).…”
Section: Introductionmentioning
confidence: 99%